JURIDICAL REVIEW ON THE ENFORCEMENT OF ILLEGAL ONLINE LENDING BASED ON THE ITE LAW AND CONSUMER PROTECTION LAW IN INDONESIA - Ahyan Septiani; Jeannie Sriamanda Putri; Zahra Maharani Mulyana (Cahaya Ilmu Bangsa, 2025)
The crime of illegal online lending has become an increasingly serious issue in Indonesia, with a growing number of victims trapped in these unlawful practices. This study aims to examine the effectiveness of legal actions against illegal online lending based on the Consumer Protection Law and the Electronic Information and Transactions Law (ITE Law). The primary focus of this research is to assess how these two regulations are applied to tackle illegal online lending crimes and the challenges encountered in the law enforcement process. The research method employed is normative juridical, utilizing both legal and conceptual approaches to analyze relevant legal provisions and understand the challenges posed by technological developments in the digital finance sector. The findings indicate that, despite clear regulations, the effectiveness of law enforcement is hindered by factors such as difficulties in monitoring online transactions, limited public awareness about the risks of illegal online lending, and obstacles in enforcing laws against cybercriminals. The study recommends strengthening regulations, implementing stricter law enforcement, and enhancing public education to improve consumer protection in the digital era.